George's marvellous medicine - Dahl, Roald; Blake, Quentin (London : Puffin Books, 2016)
The rule would be this: whatever he saw if it was runny or powdery or gooey, it went in.
Keywords: Grandmothers -- Children's stories -- Humorous Stories -- Medicine, Magic, mystic, and spagiric -- Wit and humor, Juvenile -- Children